Dual-target anti-Alzheimer's disease agents with both iron ion chelating and monoamine oxidase-B inhibitory activity. (1st January 2019) - Mi, Zhisheng; Gan, Bing; Yu, Sihang; Guo, Jianan; Zhang, Changjun; Jiang, Xiaoying; Zhou, Tao; Su, Jing; Bai, Renren; Xie, Yuanyuan
Abstract: MAO-B leads to an increase in the levels of hydrogen peroxide and oxidative free radicals, which contribute to the aetiology of the AD. Thus, both iron ion chelators and MAO-B inhibitors can be used to treat AD. Taking the coumarin derivatives and hydroxypyridinones as the lead compounds, a series of dual-target hybrids were designed and synthesised by Click Chemistry. The compounds were biologically evaluated for their iron ion chelating and MAO-B inhibitory activity. Most of the compounds displayed excellent iron ion chelating activity and moderate to good anti-MAO-B activity. Compounds 27b and 27j exhibited the most potent MAO-B inhibitory activity, with IC50 values of 0.68 and 0.86 μM, respectively. In summary, these dual-target compounds have the potential anti-AD activity.